Topology of singular fibers of differentiable maps - Saeki Osamu (Berlin Springer-Verlag, 2004)
The volume develops a thorough theory of singular fibers of generic differentiable maps. This establishes the foundational framework of the global study of singular differentiable maps of negative codimension from the viewpoint of differential topology.
Keywords: Differential topology